PENGARUH PENGGUNAAN ALAT PEMBAYARAN DENGAN MENGGUNAKAN KARTU DAN UANG ELEKTRONIK TERHADAP INFLASI DI INDONESIA TAHUN 2009-2016 - Laurentia Clara Audina Yuwono (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
his study aims to look at the effect of short-term and long-term use of card payments (ATM/Debit card and credit cards) and electronic money against inflation in Indonesia. This study uses secondary data consists of inflation, transaction volume of ATM/Debit card, transaction volume of credit card, and transaction volume of electronic money were obtained from the official website of Bank Indonesia and the Central Bureau of Statistics the period January 2009 - November 2016. This study uses regression Error Correction Model (ECM). The results showed that in the long term and short term, the transaction volume ATM / Debit card, credit card transaction volume and transaction volume of electronic money to influence the direction of inflation in Indonesia in 2009-2016.Keywords: Card Payments, Electronic Money, Inflation, Error Correction Model (ECM).